2017
DOI: 10.5888/pcd14.160548
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Food Distress and Smoking Among Racially and Ethnically Diverse Adults, Schenectady, New York, 2013–2014

Abstract: IntroductionSmoking and poor nutrition are 2 leading preventable causes of death. This study investigated associations between smoking and indicators of individual- and neighborhood-level food distress among racially and ethnically diverse urban adults.MethodsWe analyzed data from a health interview survey and a food environment assessment collected in 2013 and 2014 in Schenectady, New York. We constructed logistic regression models for current smoking with 6 indicators of food distress as exposure variables a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…17 Food insecurity is associated with substance use, specifically tobacco use, with previous studies showing a higher prevalence of cigarette smoking in low-income families in the United States with food insecurity compared to households that are food secure. [20][21][22] An analysis by Armor and colleagues in 2008 using data from the 2001 Panel Study of Income Dynamics showed that smoking was more common in low income households with food insecurity (43.6%) than in low income households that were food secure (31.9%). 20 These results suggest the presence of resource shifting from food expenditures to cigarette expenditures as a mediating factor.…”
Section: Food Insecurity and Chronic Diseasementioning
confidence: 99%
“…17 Food insecurity is associated with substance use, specifically tobacco use, with previous studies showing a higher prevalence of cigarette smoking in low-income families in the United States with food insecurity compared to households that are food secure. [20][21][22] An analysis by Armor and colleagues in 2008 using data from the 2001 Panel Study of Income Dynamics showed that smoking was more common in low income households with food insecurity (43.6%) than in low income households that were food secure (31.9%). 20 These results suggest the presence of resource shifting from food expenditures to cigarette expenditures as a mediating factor.…”
Section: Food Insecurity and Chronic Diseasementioning
confidence: 99%
“…A growing body of literature has identified significant associations between food insecurity and tobacco use, particularly cigarette smoking, with associations that are independent of demographic factors, socioeconomic variables such as income and education, and mental health variables including psychological distress (Kim and Tsoh, 2016; Hosler and Michaels, 2017; Castro et al, 2015; Sreeramareddy and Ramakrishnareddy, 2017). The relationship is hypothesized to be bidirectional and mutually reinforcing, such that spending on cigarettes worsens food insecurity, yet the psychological stress associated with food insecurity, as well as the physical feelings of hunger that occurs when food insecurity is particularly severe, may promote smoking and impede efforts at cessation.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Epidemiological studies conducted in the United States and other countries have demonstrated a relatively robust link between food insecurity and smoking. [8][9][10][11][12][13][14] The association appears to be bidirectional, with some studies showing that smoking increases the likelihood of food insecurity, [8][9][10] while other studies show that food insecurity increases the likelihood of smoking. [11][12][13] These associations remain significant after controlling for socioeconomic factors, such as income and level of education.…”
Section: Introductionmentioning
confidence: 99%